144 Investigating the molecular mechanisms of mutant C9orf72 human iPSC- derived astrocyte-mediated motor neuron deficits. Issue 6 (27th May 2022) - Stavrou, Maria; Selvaraj, Bhuvaneish; Bolado, Alfonso; James, Longden; Neil, Carragher; Margaret, Frame; Hardingham, Giles; Chandran, Siddharthan
Abstract : Amyotrophic Lateral Sclerosis (ALS) is a progressive, incurable and invariably fatal neurodegenerative condition characterised by loss of motor neurons. Over the last two decades, there are multiple lines of evidence from pathology, genetics and experimental systems that implicate a central role for non- neuronal cells, astrocytes in particular, with ALS pathogenesis. This is not surprising given the intimate structural and functional association of astrocytes with, inter alia, the synapse and vasculature. Yet, the nature of this astrocyte-neuronal crosstalk remains understudied. Harnessing the power of genetic dis- coveries combined with human iPS cellular platforms and gene editing technologies, we seek to better understand the non-cell autonomous effect of astrocytes carrying the C9orf72 mutation – the commonest genetic cause of ALS – on motor neurons. We generate human astrocytes and motor neurons from three pairs of independent patient-derived mutant C9orf72 iPSC lines and their corresponding CRISPR-Cas9 gene-edited isogenic controls. Having isogenic controls allows causality to be assigned to any given phenotype and overcomes transcriptional heterogeneity across iPSC lines. We utilise these cells to investigate astrocyte-mediated neuronal toxicity and changes in secretome profiles. By using unbiased mass spectrometric analysis and molecular tech- niques, we aim to identify the underpinning molecular mechanisms of astrocyte-mediated neuronal toxicity. This will potentially lead to the identification of putative neuroprotective targets as well as novel biomarkers. mstavrou@ed.ac.uk|NIHR Bursary 97